2017
DOI: 10.1108/jfep-12-2016-0095
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal returns from joining Congress? Evidence from new members

Abstract: Past research shows that members of Congress are informed traders, i.e., that they earn abnormal returns while in office. This important research does not identify whether being elected leads to informed trading or whether informed traders are selected into office. We try to provide a partial answer to this question by looking at whether new members of Congress were informed traders prior to being elected and how their portfolio performance changes after election and appointment to different types of committee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Our finding is consistent with research conducted bySantoso & Sri Artini (2015), who found that there were no difference between abnormal return before the 2014 legislative election and abnormal return after the event. As stated by Hall, Karadas, & Schlosky (2017), investors take no advantage on political information, or they might had reacted to the issuance of the information prior the election. Therefore, there is no more reaction during the general election.…”
Section: Resultsmentioning
confidence: 99%
“…Our finding is consistent with research conducted bySantoso & Sri Artini (2015), who found that there were no difference between abnormal return before the 2014 legislative election and abnormal return after the event. As stated by Hall, Karadas, & Schlosky (2017), investors take no advantage on political information, or they might had reacted to the issuance of the information prior the election. Therefore, there is no more reaction during the general election.…”
Section: Resultsmentioning
confidence: 99%
“…Ziobrowski et al (2011) then find that members of the US House of Representatives outperformed the market by 55 basis points a month. Their seminal work has led to a number of papers on trading by politicians (Eggers and Hainmueller, 2014;Tahoun, 2014;Hall et al, 2017;Karadas, 2018Karadas, , 2019.…”
Section: Introductionmentioning
confidence: 99%
“…The authors re-construct the portfolios of members of Congress based on their daily stock transactions (during 1993-1998 for the Senate and1985-2001 for the House) and document that these portfolios outperform the market. Further evidence in the literature reveals that local knowledge (Eggers and Hainmueller 2014), family ties (Karadas 2018), and the congressional committee powers (Hall et al 2017;Karadas 2019) affect the portfolio performance of trades reported by politicians.…”
Section: Introductionmentioning
confidence: 99%